Depression Still Requires Novel Psychiatric Medication - Maryam Kowsar; Mahmoud Mirzaei (Research Center for Rational Use of Drugs (RCRUD), 2018)
Depression is a mood disorder which leads to sadness, emptiness, loss of interest and energy for the patient. Feeling, Thinking and behaving are all influenced by the effects of depression causing a variety of emotional and physical problems in considerable numbers of people all around the world. Herein, brain chemistry plays an important role in determination and also treatment of depression for individuals. During the last decade, so many researchers have dedicated their efforts to detect the most effective potent natural products with antidepressant activities, which reveal the importance of herbal natural products to be considered as psychoactive drugs.